The Effectiveness of Using Two Stay Two Stray Learning Methods Helps Video Learning Media in Improving Student Activity - Erni, Erni Harlina Isdiati; Arif Wahyu Wirawan (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research has been set aside because of the lack of student activity in learning activities. The aim of this research is to increase student learning activity in the learning process in the classroom. This study uses the Two Stay Two Stray method with class action studies of two cycles. Each cycle takes place in two meetings with four stages of activity namely, planning, action, observation, and reflection: (1) action planning; (2) action implementation; (3) action observation; and (4) action reflection. The research was conducted in collaboration with the teacher of the Economics subjects. Students of Class X I High School of State Higher I Kartasura 36 students. Data collection techniques using observation sheets, interviews and tests. The results of the pre-cycle study showed an average student activity output of 28.92%, after cycle I action of 58.32% and increased to 85.76% in cycle II. Based on these results it can be concluded that the application of the Two Stay Two Stray method can improve the learning activity of Economics subjects. Keywords: Learning methods Two Stay Two Stray, student activity, Economics